Indonesia COVID-19 Task Force Statement Framing in September – November 2020 - Mutiara Nabila (Ikatan Sarjana Komunikasi Indonesia, 2021)
This study aims at examining how Indonesia COVID-19 Task Force, as the government's right hand man, uses Framing Theory in the press statement contents, to convince the public that the handling of COVID-19 in Indonesia has been good enough. The analysis was carried out on the content of the COVID-19 Task Force press statement from September to November 2020 when there were spikes in COVID-19 cases during that period. This research uses the social construction paradigm, to find out what kind of news framing is being carried out by the COVID-19 Handling Task Force related to news about the COVID-19 case through Murray Edelman's framing analysis. By using Murray Edelman's framing analysis, this study tries to reveal the framing of the press release of the COVID-19 Handling Task Force to form a direct public understanding that the handling of COVID-19 in Indonesia is well. The results of the analysis showed that the positive COVID-19 handling task force used a categorization framing with the titles of press statements, the majority of which only mentioned about the recovery of COVID-19 patients, such as: The Number of COVID-19 Patients Continues to Increase to 429,807 People; COVID-19 Testing Results Show 86% Confirmed Negative; Number of Testing Week Third of November Approaches WHO Standards.